2018
DOI: 10.17219/acem/68690
|View full text |Cite
|
Sign up to set email alerts
|

Impact of selected magnetic fields on the therapeutic effect in patients with lumbar discopathy: A prospective, randomized, single-blinded, and placebo-controlled clinical trial

Abstract: Background. Interdisciplinary physical therapy together with pharmacological treatment constitute conservative treatment strategies related to low back pain (LBP). There is still a lack of high quality studies aimed at an objective evaluation of physiotherapeutic procedures according to their effectiveness in LBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…A meta-analysis of surgical versus nonsurgical treatment of chronic low back pain (CLBP) suggested that nonsurgical treatment was slightly more effective, feasible, and safe [67]. Nonsurgical physical therapies like low-level laser therapy [68], magnetic therapy [11], electrical therapies [10], extracorporeal shockwave therapy [69], and high-intensity laser therapy [70] have a favorable effect on self-reported pain and functional limitations on NSLBP. These results are in line with our study, but no previous study has reported on the effect of proprioception on the lumbopelvic area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of surgical versus nonsurgical treatment of chronic low back pain (CLBP) suggested that nonsurgical treatment was slightly more effective, feasible, and safe [67]. Nonsurgical physical therapies like low-level laser therapy [68], magnetic therapy [11], electrical therapies [10], extracorporeal shockwave therapy [69], and high-intensity laser therapy [70] have a favorable effect on self-reported pain and functional limitations on NSLBP. These results are in line with our study, but no previous study has reported on the effect of proprioception on the lumbopelvic area.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of NSLBP is not fully understood [5]. Clinicians and patients were recommended by the American College of Physicians to select nonpharmacologic treatment [7] with exercise [8], multidisciplinary rehabilitation [9], electrical therapies [10], and magnetic therapy [11] to reduce pain and its consequences.…”
Section: Introductionmentioning
confidence: 99%
“…The RMQ was used to evaluate the degree of disability and state of functional condition. This questionnaire contains 24 items scored of 0 points (answer "no") or 1 point (answer "yes"), indicating lack of disability (0-3 points) or minimal (4-10); moderate (11)(12)(13)(14)(15)(16)(17) and severe disability (18)(19)(20)(21)(22)(23)(24) [20].…”
Section: Outcome Measurementsmentioning
confidence: 99%
“…The use of various nonpharmacological supportive and conservative methods in LBP management is well-known, including exercise training [5,6], manual therapies [6,7], or myofascial techniques [8]. However, effective physical agents are also needed [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…J. Taradaj и соавт. [40] показали достоверное отличие в снижении интенсивности боли при использовании активной магнитотерапии, в сравнении с ложной, у пациентов с НБС, связанной с патологией межпозвоночного диска. А. Omar и соавт.…”
Section: магнитотерапияunclassified